The locating chromatic number of (k,n)-split cycle graph and its barbell operation - Asmiati, Asmiati; Prawinasti, Kasandra; Damayanti, Maharani; Yulianti, Lyra (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2025)
The locating chromatic number remains an active topic in graph theory. It combines the concepts of partition dimension and proper vertex coloring. A necessary condition for determining the locating chromatic number is that each vertex must have a unique color code under a minimal coloring. This paper investigates the locating chromatic number of the (k,n)-split cycle graph and its barbell operation.